1977
DOI: 10.1152/ajpcell.1977.232.3.c109
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and chloride conductances in normal and denervated rat muscles

Abstract: The membrane conductance of rat muscles (mainly gastrocnemius (G) and soleus (S)) was measured by using the two-microelectrode technique and the current point clamp method. Thin muscle bundles were washed in Tris chloride and Tris propionate solutions containing 6 mM K. The current strength was always 5 x 10-9 A and the steady-state membrane voltage was about 5 mV. The average chloride conductance (gcl, in mumho/cm2) of normal muscles was 845 (G) and 1,025 (S). The potassium conductance (gk) was 99 (G) and 161… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The effect of denervation upon Clchannels has also been studied. Total Clconductance is decreased by denervation (Camerino & Bryant, 1976;Lorkovic & Tomanek, 1977), but the distribution of Clchannels is unaltered (Betz, Caldwell & Harris, 1986). Denervation also affects mammalian Na+ channels, resulting in the appearance of channels with slowed kinetics and reduced sensitivity to the blocking action of tetrodotoxin (TTX) (Redfern & Thesleff, 1971;Pappone, 1980;Hollingworth, Marshall & Robson, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of denervation upon Clchannels has also been studied. Total Clconductance is decreased by denervation (Camerino & Bryant, 1976;Lorkovic & Tomanek, 1977), but the distribution of Clchannels is unaltered (Betz, Caldwell & Harris, 1986). Denervation also affects mammalian Na+ channels, resulting in the appearance of channels with slowed kinetics and reduced sensitivity to the blocking action of tetrodotoxin (TTX) (Redfern & Thesleff, 1971;Pappone, 1980;Hollingworth, Marshall & Robson, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle membrane becomes sensitive to ACh along its entire length (Axelsson & Thesleff, 1959;Miledi, 1960) due to an increase in the rate of AChR synthesis and its incorporation into the extrajunctional membrane (see Fambrough, 1979). In addition, the chloride conductance of denervated muscle is decreased from that of innervated muscle (Westgaard, 1975;Camerino & Bryant, 1976;Lorkovic & Tomanek, 1977;Harris & Betz, 1987). The experiments described in this paper showed that AChR and the chloride channel responsible for resting membrane conductance were regulated anticoordinate to one another.…”
Section: Introductionmentioning
confidence: 85%
“…Since blocking Gci in normal muscle with 9-AC greatly reduces the steady current (Betz et al 1984b), and since Gci falls 2-5-fold after denervation (Camerino & Bryant, 1976;Lorkovic & Tomanek, 1977), one might have predicted that the current would be reduced or abolished by denervation. All of the results suggested that the mechanism is essentially unchanged after denervation.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this difference is unknown; perhaps K+ conductance becomes insensitive to removal of external K+ after denervation, so that Vm follows changes in EK more closely (cf. Lorkovic & Tomanek, 1977).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation